Effect of food variety on intake of a meal: a systematic review and meta-analysis. Issue 3 (29th January 2021) - Embling, Rochelle; Pink, Aimee E; Gatzemeier, Jennifer; Price, Menna; D Lee, Michelle; Wilkinson, Laura L
ABSTRACT: Background: Many studies have shown that food variety—the presence of multiple foods and/or sensory characteristics within and across meals—increases intake. However, studies report mixed findings, and effect size remains unclear. Objectives: A systematic review and meta-analysis were conducted to 1 ) synthesize data across experimental studies that examined effects of variety on total meal intake, relative to a control condition with comparatively less variety; 2 ) quantify support for this effect; and 3 ) assist in the identification of important moderating factors (registration: CRD42019153585). Methods: In November 2019, we searched the following databases for relevant experimental studies, published in English from 1980, with human participants: PubMed, Cochrane Library, Web of Science, ClinicalTrials.gov, PsycINFO, and OpenGrey. This search was updated in September 2020. Means, standard deviations, and sample sizes were extracted from included articles, and Hedges' g was used to calculate effect sizes. Risk of bias was assessed using the Cochrane Collaboration's tool. Results: Of 7259 references identified in an initial search, 34 articles consisting of 37 studies contained sufficient information for review, and data from 30 studies (39 comparisons) were included in the meta-analysis. Results from a random-effects model showed a significant small to medium effect of variety on intake (in weight and energy), with greater variety being associated with increased consumption (Hedges' g = 0.405; 95% CI: 0.259, 0.552). However, heterogeneity was considerable across studies ( I 2 = 84%), and this was unexplained by subgroup analyses based on form of variety, test foods, sensory characteristics, age, sex, and body weight. Conclusions: Our findings support the conclusion that variety is a robust driver of food intake. However, risk of bias was high across studies, and this review highlights methodologic limitations of studies. It is recommended that further attention is given to the development of preregistered, well-powered randomized controlled studies in eating behavior research.